( The development of a Non Dsctructive Electrical Technique to Assess Banana Quality) - Susanto, Eko (Warta Industri Hasil Pertanian, 1988)
The variation of the dielectric properties of bananas was applied for measuring their quality. The loss tangent was express the degree of banana maturity. Other quality factors measured were sugar and moisture content, pH, pulp to peel ratio and texture. Destructive and non destructive methods were studied to investigate the realtionship between them. The non destructive method was performed by inserting two blades into the banana. Quantitative and quallitative changes of banana were measured with approximately linear correlation with the loss tangent as measured with a universal bridge. The analysis showed that the loss tangent of the banana decreased during the maturation period. The best correlation between sugar content and the loss tangent existed with a linear correlation of 0.93.Â